Investment in Disaster Risk Management in Europe Makes Economic Sense : Background Report - World Bank (World Bank, Washington, DC, 2021)
This report forms part of the World Bank’s technical assistance project undertaken with the European Commission’s Directorate-General for European Civil Protection and Humanitarian Aid Operations (DG ECHO) and financed under the Union Civil Protection Mechanism (UCPM) Annual Work Program 2020. This report is the output produced under Component 1, ‘Retrospective analysis of the costs and benefits of selected disaster risk management (DRM) investments’, with the aim to showcase the benefits of investing in the prevention of disaster risks. The objective of this report is to provide EU Member States/Participating States (MS/PS) and UCPM members with consolidated analysis and information on the economic value of investing in disaster and climate preparedness and prevention. The analysis can serve as a basis for (i) demonstrating the net benefits of investing in prevention and preparedness for various hazards, (ii) showcasing best practices in investing in prevention for various MS/PS and UCPM members as well as at a regional scale, and (iii) providing guidance on methodological approaches to estimate the net benefits of interventions, including soft investments, with a focus on the application of the Triple Dividend of Resilience framework for economic analysis (Tanner, et al., 2015), though other methodologies are also described in this report. Although the report mainly focuses on Europe, international examples are presented throughout.